PEMIKIRAN MAHMUD YUNUS TENTANG KONSEP PENDIDIKAN ISLAM - Fauza Masyhudi (JURNAL TARBIYAH, 2014)
Islamic education is still faced with many problems that include components, such as educators, learners, methods, curriculum and others. Related to this issue, it takes ideas to solve the problem. Discussion about education leaders recognize that Islam is not just his life, but also their thoughts on Islamic education. Their thought still need to be assessed, although this time the human race in the modern era because it could be some of the results of their thinking is still relevant for use today to solve the problem of Islamic education. One of the figures was Mahmud Yunus